2018
DOI: 10.1016/j.nicl.2018.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity is associated with left corticospinal tract microstructure in bipolar depression

Abstract: Psychomotor retardation and reduced daily activities are core features of the depressive syndrome including bipolar disorder (BD). It was the aim of this study to investigate white matter microstructure of the motor system in BD during depression and its association with motor activity. We hypothesized reduced physical activity, microstructural alterations of motor tracts and different associations between activity levels and motor tract microstructure in BD. Nineteen bipolar patients with a current depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…A change in RK instead of AK is thought to indicate that a more pronounced alteration occurs in the direction perpendicular to the principal axis of white matter axons. An increase in oligodendrocyte density or cell clustering of astrocytes may be responsible . Antidepressant medication may be implicated in BD patients .…”
Section: Discussionsupporting
confidence: 82%
“…A change in RK instead of AK is thought to indicate that a more pronounced alteration occurs in the direction perpendicular to the principal axis of white matter axons. An increase in oligodendrocyte density or cell clustering of astrocytes may be responsible . Antidepressant medication may be implicated in BD patients .…”
Section: Discussionsupporting
confidence: 82%
“…Few studies have examined neural correlates of psychomotor retardation in MDD and BD and found brain alterations in functional and structural networks, mainly including the motor circuitry (Bracht et al, 2018;Buyukdura et al, 2011;Koo et al, 2019;Martino et al, 2020;Walther et al, 2012aWalther et al, , 2012b. There is some evidence suggesting distinct neural differences between unipolar and bipolar depression (Diler et al, 2014;Han, De Berardis, Fornaro, & Kim, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether this difference pertains to psychomotor retardation, as very few studies have directly compared its correlates between the two diagnoses (Cantisani et al, 2016). Also in neuroimaging studies, actigraphy has proven to be an informative measure of psychomotor disturbance when exploring brain-behavior associations (Bracht et al, 2012(Bracht et al, , 2018Cantisani et al, 2016;Walther et al, 2012aWalther et al, , 2012b.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted MRI (DW-MRI) data were analyzed using ExploreDTI 4.8.6 58 . Data were pre-processed as described in previous publications 59 , 60 . In short, a subjection motion and distortion correction and an EPI-correction was performed 61 .…”
Section: Methodsmentioning
confidence: 99%